Effect of Different non Starch Polysaccharides in Semi Purified Diets on Performance and Intestinal Microflora of Young Broiler Chickens - Shakouri, M.D.; Kermanshahi, H.; Mohsenzadeh, M. (International Journal of Poultry Science, 2006)
An experiment was conducted with broiler chickens to study the effect of different non starch polysaccharides; NSPs (cellulose, pectin and carboxymethyl cellulose; CMC) on growth performance and intestinal microflora. 96 day-old male chickens were allocated to 4 experimental diets (a semi purified control diet or diets containing 3% of above mentioned NSPs) in a completely randomized design for two weeks. On day 10, one bird from each replicate was slaughtered to remove the intestinal contents for microbial analyses. According to the results, total feed intake over 2 weeks was increased (P< 0.0001) as a result of cellulose addition to the diet. The final body weight and also feed conversion ratio of chickens on this diet were improved (P< 0.0001). Growth performance parameters were dramatically declined by CMC (P< 0.0001). Pectin significantly (P< 0.001) increased the number of total anaerobes in the duodenum. CMC resulted in higher caecal number of Enterobacteriaceae (P< 0.001). Compared to the control diet, all NSPs decreased the number of lactic acid bacteria in the intestinal segments. Under the conditions of this study, it was concluded that different NSPs are acted differently on performance and intestinal microflora when imposed to broiler chickens.